La fine dell’eccezione atlantica e la decolonizzazione dell’Europa - Margarida Calafate Ribeiro (Confluenze, 2014)
Since its foundation Portugal has been seen by others and by itself as, in the words of Eduardo Lourenço, an “uncommon Portuguese exception”. An exception that has historically become a norm firstly built upon the relationship with both the physical and political body of Iberia, leading afterwards to the independence of the Reign of Portugal. This independence was perceived as an achievement gained through the exceptional and narratively miraculous Battle of Ourique and reaffirmed then thanks to the equally miraculous Battle of Aljubarrota. This sort of vocation for 'exceptionality' was inherent in the geography of the country itself, as Zurara emphasized in ancient times in the first chronicle of its expansion: the Crónica da Tomada de Ceuta.